Morphological Dynamics of Leukemia Cells on TiO2 Nanoparticle Coatings Studied by AFM - Garcia Diosa, Jaime Andres; Gonzalez Orive, Alejandro; Grundmeier, Guido; Camargo Amado, Ruben Jesus; Keller, Adrian (Applied Sciences)
Coatings of modified TiO2 nanoparticles (TiO2-m) have been shown to effectively and selectively trap non-adherent cancer cells, with an enormous potential for applications in photodynamic therapy (PDT). Leukemia cells have a remarkable affinity for TiO2-m coatings, adhering to the surface by membrane structures and exhibiting morphologic characteristics of amoeboid locomotion. However, the details of the cell–substrate interaction induced by the TiO2-m coating remain elusive. With the aim to obtain a better understanding of this phenomenon, leukemia cell adhesion to such coatings was characterized by atomic force microscopy (AFM) for short contact times up to 60 min. The cell and membrane morphological parameters mean cell height, contact area, cell volume, and membrane roughness were determined at different contact times. These results reveal cell expansion and contraction phases occurring during the initial stage of adhesion. Subsequently, the leukemic cells reach what appears to be a new resting state, characterized by pinning of the cell membrane by TiO2-m nanoparticle aggregates protruding from the coating surface.